2003
DOI: 10.1091/mbc.e02-12-0823
|View full text |Cite
|
Sign up to set email alerts
|

STAM Proteins Bind Ubiquitinated Proteins on the Early Endosome via the VHS Domain and Ubiquitin-interacting Motif

Abstract: Conjugation with ubiquitin acts as a sorting signal for proteins in the endocytic and biosynthetic pathways at the endosome. Signal-transducing adaptor molecule (STAM) proteins, STAM1 and STAM2, are associated with hepatocyte growth factor-regulated substrate (Hrs) but their function remains unknown. Herein, we show that STAM proteins bind ubiquitin and ubiquitinated proteins and that the tandemly located VHS (Vps27/Hrs/STAM) domain and ubiquitin-interacting motif serve as the binding site(s). STAM proteins co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
96
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(101 citation statements)
references
References 55 publications
(108 reference statements)
5
96
0
Order By: Relevance
“…Cooperativity of neighbor ubiquitin-binding domains has recently been observed in the signal transducing adaptor molecule 2 (STAM2), one of the ESCRT-0 subunits that coordinate the proper function of the ESCRT protein complex responsible for committing ubiquitinated cargo to the multivesicular body pathway (40). STAM2 possesses two ubiquitin-binding domains, the VHS domain and the ubiquitin-interacting motif, which are separated from each other by a linker of 20 amino acids (41). Also, we observed that the affinity of Tollip for PtdIns(3)P is about 10-fold higher than ubiquitin.…”
Section: Discussionmentioning
confidence: 99%
“…Cooperativity of neighbor ubiquitin-binding domains has recently been observed in the signal transducing adaptor molecule 2 (STAM2), one of the ESCRT-0 subunits that coordinate the proper function of the ESCRT protein complex responsible for committing ubiquitinated cargo to the multivesicular body pathway (40). STAM2 possesses two ubiquitin-binding domains, the VHS domain and the ubiquitin-interacting motif, which are separated from each other by a linker of 20 amino acids (41). Also, we observed that the affinity of Tollip for PtdIns(3)P is about 10-fold higher than ubiquitin.…”
Section: Discussionmentioning
confidence: 99%
“…Both Hrs and STAM bind ubiquitin via ubiquitin-interacting motifs (66 -68). STAM also contains a VHS domain reported to interact with ubiquitin (68). Ubiquitin binding by STAM and Hrs is thought to be essential for the efficient sorting of ubiquitinated membrane proteins (33,64,67,69).…”
Section: Discussionmentioning
confidence: 99%
“…Endosomal sorting of ubiquitinated RTKs is initiated by a complex of two Ub-binding proteins, hepatocyte growth factor-regulated substrate (Hrs) and signal-transducing adaptor molecule (STAM), which localizes on the cytoplasmic face of the early endosomal membrane (Komada et al, 1997;Bache et al, 2003b;Mizuno et al, 2003Mizuno et al, , 2004. Depletion of Hrs or STAM using RNA interference (RNAi) or gene disruption inhibits RTK down-regulation in mammalian cells (Bache et al, 2003b;Hammond et al, 2003;Kanazawa et al, 2003;Lu et al, 2003) and in Drosophila (Lloyd et al, 2002).…”
Section: Introductionmentioning
confidence: 99%